SILICON CONTENT, PHYSICAL AND CHEMICAL PROPERTIES OF SOILS OF THE KHMELNYTSKY REGION OF UKRAINE - Тоnkha, O.; Bykova, O.; Pikovska, O.; Fedosiy, I.; Menshov, O.; Shepel, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Silicon plays the significant role in the growth and development of plants, their resistance to stress conditions. However, there is limited research on the content of various forms of silicon in soils, the relationship with soil cations, which is particularly relevant in the context of intensive agriculture and climate aridization in Ukraine. The purpose of the present study was to determine the content of silicon compounds of different mobility in the arable soils of the Khmelnytsky region, the spatial variation of these parameters, and to detect the dependence between the content of silicon compounds and soil particle size. The study was performed at the area of LLC "Lotivka Elit" of Shepetivka district of Khmelnitsky region in field crop rotation. We determined for soil samples: particle size distribution and content of fractions of granulometric elements of different sizes, pH of salt extraction (1,0 M KCl solution), humus content, calcium and magnesium exchangeable compounds by extraction with 1,0 M KCl solution. The results showed that the content of silicon compounds in soils depends on the particle size distribution of soil, the value of exchangeable acidity, humus content, and the composition of exchangeable cations.
Keywords: silicon; soil cations; soil reaction; exchangeable cations; soil texture